Pembuatan Aplikasi Manajemen Persediaan ATK Berbasis Excel Visual Basic di PT PLN PUSHARLIS Kantor Induk - Salma, Aliya; Chaniago, Harmon (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Office activities are closely related to various equipment needed. Office Stationery (ATK) is an important need that must be met for an agency and its use needs to be properly supervised because it acts as the main supporting facility in carrying out the administration process. The ATK inventory management system at PLN PUSHARLIS has been computerized, but there are still several weaknesses in terms of data input and preparation of inventory reports so that there is no automation process and there is no certainty of recording accuracy. This project aims to (1) Determine the initial condition of office stationery inventory management, (2) Design and create an application, and (3) Implement the application at PT PLN PUSHARLIS Main Office. This project uses the waterfall method. Data collection techniques are carried out by direct observation and conducting interviews, and are supported by data obtained from actual field conditions. The application is designed and created using Microsoft Excel Visual Basic. This application has several main features in the form of a goods database, interactive dashboard, recording of incoming and outgoing goods, and automatic reporting of goods inventory. Based on the test results using the blackbox testing method and supported by the results of the usability testing questionnaire, the application runs well without any errors and can be used as a tool in managing office stationery more efficiently. In addition, the informative interface makes this application easy to understand and use by users.